PP.26.06: SAFETY AND PERFORMANCE OF THE NEXT GENERATION ENLIGHTN RENAL DENERVATION SYSTEM IN PATIENTS WITH DRUG-RESISTANT HYPERTENSION. (June 2015) - Worthley, S.; Wilkins, G.; Webster, M.; Montarello, J.; Antonis, P.; Whitbourn, R.; Warren, R.
Abstract : Objective: Catheter-based renal artery denervation therapy is under evaluation as a therapeutic option in patients with resistant hypertension. We further investigated the safety and performance of the next generation EnligHTN™ Renal Denervation System (St. Jude Medical) in patients with drug-resistant hypertension. Design and method: The EnligHTN Renal Artery Ablation Catheter has 4 electrodes attached on a basket mounted at the tip of the catheter. The next generation EnligHTN RF Ablation Generator utilises a novel algorithm for the delivery of 1 minute of radiofrequency energy, optimised for simultaneous delivery of therapy through all 4 electrodes, with an interactive, intuitive user interface. Renal denervation was performed on 39 patients across 6 centres meeting the following inclusion criteria: 18–80 years of age, an office systolic BP > 160 mmHg, an average daytime systolic ambulatory BP > 135 mmHg, on three or more antihypertensive agents (including a diuretic), and renal artery diameter > 4 mm and length > 20 mm. Renal artery CT angiography was repeated at 6 months in all patients. Results: To date 18/38 patients have completed 18-months of follow-up post procedure. Through 12 months of follow-up, there were no serious device related adverse events during the procedure, including no renal artery damage (i.e. no renal artery dissections, aneurysms, flow limiting renal artery vasospasms, or renal artery stenosis) as adjudicated by an independent Clinical Events Committee. There was one reported serious procedure related vascular access site complication (pseudoaneurysm of the femoral artery) which resolved after manual compression and thrombin injection. There were no clinically significant changes in renal function through 12-months as observed in eGFR, serum creatinine, cystatin C, or urine albumin-to-creatinine ratio. 18-month office BP reductions from baseline are thus far -24.2/-9.5 mmHg, which are statistically significant. Renal artery denervation procedures were performed successfully in all patients, with an average of 4.33 ablation sets and 15.85 ablations performed per patient. Conclusions: After 12-months follow-up post procedure in this first-in-human study, we conclude that data demonstrates the next generation EnligHTN Renal Denervation System continues to be safe, rapid, and effective in the treatment of patients with drug-resistant, uncontrolled hypertension.